Neutrophil/lymphocyte ratio and lymphocyte/monocyte ratio in ulcerative colitis as non-invasive biomarkers of disease activity and severity - Okba, Ashraf M. (Auto Immun Highlights, 2019)
BACKGROUND: Apart from endoscopic interventions, readily attainable cost-effective biomarkers for ulcerative colitis (UC) assessment are required. For this purpose, we evaluated differential leucocytic ratio, mainly neutrophil–lymphocyte ratio (NLR) and lymphocyte-monocyte ratio (LMR) as simple available indicators of disease activity in patients with ulcerative colitis. METHODS: Study conducted on 80 UC patients who were classified into two groups of 40 each according to Mayo score and colonoscopic findings. Group 1 (active UC) and group 2 (inactive UC). Another 40 group-matched healthy participants were enrolled. White blood cell count, NLR, LMR, C-reactive protein, and Erythrocyte sedimentation rate were measured and recorded. RESULTS: Significant elevation of NLR was observed in active UC group compared to inactive UC and controls (2.63 ± 0.43, 1.64 ± 0.25, 1.44 ± 0.19 respectively; p < 0.0001). The optimal NLR cut-off value for active UC was > 1.91, with a sensitivity and a specificity of 90% and 90% respectively. The mean LMRs of active UC was significantly lower compared with inactive UC patients and controls (2.25 ± 0.51, 3.58 ± 0.76, 3.64 ± 0.49 respectively; p < 0.0001). The cut-off value of LMR for determining the disease activity was ≤ 2.88 with a sensitivity of 90% and a specificity of 90%. NLR, LMR, and CRP were found to be significant independent markers for discriminating disease activity (p = 0.000). Besides, NLR was significantly higher in patients with pancolitis and positively correlated with endoscopically severe disease. CONCLUSION: NLRs and LMRs are simple non-invasive affordable independent markers of disease activity in UC.